Incidence and spectrum of infections among HIV/AIDS patients with lymphoma during chemotherapy. Issue 10 (October 2021) - Wang, Zhenyan; Zhang, Renfang; Liu, Li; Shen, Yinzhong; Chen, Jun; Qi, Tangkai; Song, Wei; Tang, Yang; Sun, Jianjun; Lin, Yixiao; Xu, Shuibao; Yang, Junyang; et al.
Abstract: Introduction Lymphoma is the most common cancer in HIV/AIDS patients. Chemotherapy regiments recommended for lymphomas in HIV-negative patients are also used for lymphomas in HIV/AIDS patients. Little is known about the infections among HIV/AIDS patients with lymphoma undergoing chemotherapy. Methods This retrospective study investigated the incidence, spectrum of and risk factors for infections during chemotherapy in 164 HIV/AIDS patients with lymphoma admitted to Shanghai Public Health Clinical Center from July 2013 to December 2020. Results The median age of the patients was 43 years old; 90.9% (149/164) were male. A total of 112 (68.3%) patients had a CD4 count < 200 cells/μL at lymphoma diagnosis. Diffuse large B-cell lymphoma (56%, 91/164) and Burkitt lymphoma (28%, 46/164) were the two most common subtypes of lymphoma. Among the 137 patients who underwent chemotherapy (total cycles = 749), 58.4% (80/137) of patients experienced a total of 153 episodes of infection, with an incidence rate of 20.4% (153/749). The most commonly seen infections were lung infection (29.2%, 40/137) and febrile neutropenia (27.0%, 37/137). Multivariate analysis showed that grade 4 neutropenia during chemotherapy (OR = 7.128, 95% CI 3.051–16.654, p < 0.001) and duration of antiretroviral treatment at lymphoma diagnosis <6 months (OR = 3.520, 95% CI 1.432–8.653, p = 0.006) were independent risk factors for infection during chemotherapy. Conclusions A large proportion of HIV/AIDS patients with lymphoma may be at risk of infection during chemotherapy. Effective measures should be taken for patients with high risk factors to prevent the occurrence of infection.